Penilaian Peran serta Masyarakat dalam Akselerasi Penurunan Angka Kematian Ibu dan Angka Kematian Bayi - Niniek L. Pratiwi (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background and Methods: This research analyzed the assessment of community organizations in efforts to accelerate the decrease of maternal and infant mortality rates (MMR and IMR). This was an explorative study using qualitative and quantitative data. It was conducted in four provinces: Central Kalimantan, South Sulawesi, Central and East Java. In each province two districts were selected with criteria of high MMR and IMR, and low MMR and IMR.Result and Conclusion: Results showed that the roles of community organizations to accelerate the decrease of MMR and IMR limited in promoting and providing education to overcome four excesses (4 terlalu) and three delays (3 terlambat). The organizations considered these roles were not enough, and also the utilization of budget to these activities was not optimal. In the future the community organizations applying community participation should enhanced the members’ senses of belonging by active participation in planning process starting from problems identification until factual contributions to achieve higher social concerns so that the five steps changing of an innovation could be achieved.Keywords: community organization, powerful community